The Development Of High Temperature Recirculating Pump (HTRP) For Energy Savings In An Incinerator. - Hassan Mohamed, Noorul Ameen; Zakaria, Ridzuan; Muhd Yunus, Muhd Noor (2006)
Tremendous increase in generation of Municipal Solid Waste (MSW) has become a major concern for the Ma-laysian government as the country experiencing rapid development. It was estimated about 16000 tones/day MSW is produced at national level and in Kuala Lumpur alone about 2500 tones/day.